ANALISIS PENGARUH PELATIHAN, PENGEMBANGAN, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BANK MEGA KCP SERANG - Angrian Permana (Universitas Mercu Buana, 2013)
Abstract: The objective of this research were to know the influence of training,development, and compensation towards employee performance of Bank Mega SerangSub Branch. The sample of this reserach were forty four by using census method. Theresearch result showed that training have positive and significant influence onemployee performance, material dimension is the most affect dimension on employeeperformance. Development have positive and significant influence on employeeperformance, formal development is the most affect dimension on employeeperformance. Compensation have positive and significant influence on employeeperformance, financial, especially for base salary is the most affect dimension onemployee performance.Key Words: Training, Development, Compensation, Employee Performance